STRATEGIES OF ISLAMIC EDUCATION TEACHERS IN INSTILLING MULTICULTURAL VALUES IN STUDENTS - Irsyaad, Aufaa Muhammad; Mashudi, Mashudi; Nawangsari, Dyah; Aniaty, Ana (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
Indonesia is a nation endowed with extraordinary ethnic, religious, and cultural diversity. In this context, education serves as a strategic medium for instilling multicultural values in the younger generation. Islamic Education (PAI) teachers play a crucial role in shaping students’ attitudes toward diversity, tolerance, and inclusiveness through universal Islamic teachings. This study aims to identify the strategies employed by PAI teachers in fostering multicultural awareness among students. Using a qualitative approach, the findings indicate that group discussions, the integration of Islamic values into the curriculum, and cross-cultural activities significantly assist students in understanding and appreciating differences. The study also highlights the challenges faced by PAI teachers in implementing these strategies, such as limited time and a lack of specialized training. Recommendations for enhancing teacher training and developing multicultural-based curricula emerged as key findings of this research.